2017
DOI: 10.1111/jan.13513
|View full text |Cite
|
Sign up to set email alerts
|

A peer learning intervention targeting newly graduated nurses: A feasibility study with a descriptive design based on the Medical Research Council framework

Abstract: This peer learning intervention seems to be feasible in this context. This study will serve as the basis for a future full-scale evaluation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Educational interventions focusing on self‐directed and self‐regulated learning (Saks & Leijen, ) might support students’ ability to self‐assess and self‐reflect, thereby improving their learning conditions. For example, the pedagogical model peer learning, which is characterized by a two‐way, reciprocal learning activity supporting abilities like self‐assessment and peer assessment as well as communication and articulation of own knowledge, understanding, and skills (Boud, Cohen, & Sampson, ; Pålsson, Engström, Leo Swenne, & Mårtensson, ). In relation to the clinical education of undergraduate nursing and other health science students, peer learning has demonstrated improved nursing self‐efficacy (Pålsson, Mårtensson, Swenne, Adel, & Engström, ) and self‐evaluation (Secomb, ), for example.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions focusing on self‐directed and self‐regulated learning (Saks & Leijen, ) might support students’ ability to self‐assess and self‐reflect, thereby improving their learning conditions. For example, the pedagogical model peer learning, which is characterized by a two‐way, reciprocal learning activity supporting abilities like self‐assessment and peer assessment as well as communication and articulation of own knowledge, understanding, and skills (Boud, Cohen, & Sampson, ; Pålsson, Engström, Leo Swenne, & Mårtensson, ). In relation to the clinical education of undergraduate nursing and other health science students, peer learning has demonstrated improved nursing self‐efficacy (Pålsson, Mårtensson, Swenne, Adel, & Engström, ) and self‐evaluation (Secomb, ), for example.…”
Section: Discussionmentioning
confidence: 99%
“…The controversy surrounding self-learning and peer-to-peer learning (based on the transmission of knowledge among equals) has been a subject of debate [14]. Despite being an important complement to teaching time, some believe that self-learning by itself cannot replace guided learning [15]. MAES© was designed with the aim that students learn in a collaborative way, which should have a subjective impact on communication skills and possibly increase teamwork skills [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that new graduates who have the opportunity to meet, socialize and share experiences assist each other in coping with stress [ 2 ]. Furthermore, that having a peer involved sharing and acknowledging each other’s experiences and feelings, asking each other as they say “stupid questions”, and admitting to shortcomings and worries, all of which reduced feelings of stress and anxiety [ 3 ]. The present study is part of a research project designed to investigate new graduates’ pathways into the profession.…”
Section: Introductionmentioning
confidence: 99%
“…It focuses on the use, feasibility and effects of peer learning. The conclusion from our earlier feasibility study was that the peer learning intervention seemed to be feasible in the study context [ 3 ]. The present study is an extension and aims to look at the process and effect of using a peer learning intervention in workplace introduction for new graduates.…”
Section: Introductionmentioning
confidence: 99%